Assisting Victims of Terrorism Towards a European Standard of Justice - Letschert, Rianne; Pemberton, Antony; Staiger, Ines.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The large-scale terrorist attacks on 9/11 resulted in more attention being devoted to victims of terrorist acts. Discussions took place on how their needs could be best accommodated. The Madrid bombings in March 2004 gave further impetus to this process. This development is also part of a recent trend towards general victim of crime policies that branch out into specialized policies devised to meet the needs of particular groups of victims such as victims of trafficking, victims of sexual violence and abuse or victims of traffic accidents. However, although a movement of national and international solidarity relating to addressing the needs of victims of terrorism has developed, political consensus is still fragile. This book provides a thorough analysis of the specific needs of victims of terrorism (using both legal and psycho-social studies), compared to victims of other forms of crime. The study combines different disciplines, enabling to combine the different perspectives leading to synergy in the analysis of the legal and psycho-social needs of victims of terrorism. Furthermore the appropriateness of restorative justice practices in the context of terrorism is included and provides challenging new insights.
I. Introduction and Definitions -- 1. The Aim of the Study. 2. Methodology. 3. Contemporary Terrorism. 4. Defining Terrorism. 5. Defining Victims of Terrorism. 6. Defining Restorative Justice. 7. Concluding Observations. Bibliography -- II. International Initiatives and Activities focusing Specifically on Victims of Terrorism, including Exising International Instruments -- 1. Introduction into General Victims' Rights. 2. International Activities and Instruments. 3. Analysis of the Legal Status of EU Standards for Victims of Terrorism. 4. Justifying EU Involvement. 5. Concluding Observations. Appendix CoE Guidelines on the Protection of Victims of Terrorist Acts. Appendix UN Van Boven/ Bassiouni Principles. Bibliography -- III. Needs of Victims of Terrorism -- 1. Introduction: Consequences of Terrorist Victimisation and Needs of Victims of Terrorism. 2. The Needs of Victims. 3. The Differential Impact of Terrorism and related Needs. 4. Vicarious Victims and the Intergroup Context. Concluding Observations. Bibliography -- IV. Psyco-Social Assitance -- 1. Introduction. 2. A Stepped Care Approach to Mass Victimisation of Terrorism. 3. Community-based Interventions. 4. Information and Coomunication. 5. Concluding Observations. Bibliography -- V. Access to Justice and Administration of Justice -- 1. Introduction. 2. Access to Justice. 3. Administration of Justice. 4. Participation Rights for Victims of Terrorism. 5. Concluding Observations -- VI. Compensation -- 1. Introduction. 2. European Instruments relating to Compensation for Victims of Crime and Terrorism. 3. National State Compensation Funds for Victims of Crime in General. 4. Specific State Compensation Funds for Victims of Terrorism. 5. Ad Hoc Compensation Funds: The Victim Compensation Fund of 11 September 2001(VCF). 6. International Trust Funds. 7. Private Remedies. 8. Compensation through Criminal Proceedings. 9. Reparation for Victims of Terrorism. Concluding Observations. Bibliography. Appendix -- VII. Restorative Justice and Victims of Terrorism -- 1. Introduction. 2. Restorative Justice Principles and Values. 3. A Framework for Restorative Justice. 4. Restorative Justice Practices. 5. The Potential of Restorative Justice Practices for Victims of Terrorism. 6. Restorative Justice Responses to Terrorism. 7. Restorative Justice Practices in Context. 8. Towards a Conceptual Framework for Restorative Justice Processes for Victims of Terrorism at the Micro-, Meso- and Macro-level. 9. Towards a Global Restorative Justice Strategy in the Terrorism Context. 10. Concluding Observations. Bibliography.
Keywords: Law; Criminal Law; Humanities; Law -- Psychological aspects; Law; Private International Law, International & Foreign Law, Comparative Law; Law and Psychology; Public International Law; Criminal Law; Interdisciplinary Studies